Dysphagia in acute stroke. - Gordon, C (1987)
A prospective study was undertaken to define the incidence, duration, and consequences of dysphagia in an unselected group of 91 consecutive patients who had suffered acute stroke. The site of the present lesion and of any previous stroke was determined clinically and was confirmed by computed tomography of the brain or necropsy in 40 cases. Of 41 patients who had dysphagia on admission, 37 had had a stroke in one cerebral hemisphere. Only seven patients showed evidence of lesions in both hemispheres. Nineteen of 22 patients who survived a stroke in a hemisphere regained their ability to swallow within 14 days. Dysphagia in patients who had had a stroke in a cerebral hemisphere was associated in this study with a higher incidence of chest infections, dehydration, and death.